2017
DOI: 10.1371/journal.pone.0168775
|View full text |Cite
|
Sign up to set email alerts
|

Arginine and Lysine Transporters Are Essential for Trypanosoma brucei

Abstract: For Trypanosoma brucei arginine and lysine are essential amino acids and therefore have to be imported from the host. Heterologous expression in Saccharomyces cerevisiae mutants identified cationic amino acid transporters among members of the T. brucei AAAP (amino acid/auxin permease) family. TbAAT5-3 showed high affinity arginine uptake (Km 3.6 ± 0.4 μM) and high selectivity for L-arginine. L-arginine transport was reduced by a 10-times excess of L-arginine, homo-arginine, canavanine or arginine-β-naphthylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…TbAAT5-3 and TbAAT16-1 have been heterologously expressed, showing high affinity for Arg and Lys (in both cases K M in the low µM range) and high selectivity (including stereoselectivity, the D-isomer does not affect the transport). Peculiarly, down-regulation of these transporters affected BSF growth, demonstrating they are essential for the parasites [ 45 ]. In addition, it has been shown that T. brucei has two high-affinity Orn transporters, TbAAT10-1 and TbAAT2-4.…”
Section: Amino Acid Uptakementioning
confidence: 99%
“…TbAAT5-3 and TbAAT16-1 have been heterologously expressed, showing high affinity for Arg and Lys (in both cases K M in the low µM range) and high selectivity (including stereoselectivity, the D-isomer does not affect the transport). Peculiarly, down-regulation of these transporters affected BSF growth, demonstrating they are essential for the parasites [ 45 ]. In addition, it has been shown that T. brucei has two high-affinity Orn transporters, TbAAT10-1 and TbAAT2-4.…”
Section: Amino Acid Uptakementioning
confidence: 99%
“…Interestingly, arginine kinase and arginine N -methyl transferase genes were overexpressed in Tbg isolated from tsetse flies ( 127 ), as if targeting l -arginine were a metabolic key in the developmental life cycle of African trypanosomes. l -Arginine transporters were also defined as essential for trypanosomes ( 128 ). Differences in arginase subcellular locations between Tbb and in T. cruzi have been reported ( 129 , 130 ), but their biological significance remains to be determined.…”
Section: Macrophage L -Arginine Metabolism Dysregumentioning
confidence: 99%
“…The loss of TbAAT6 is sufficient to develop resistance to eflornithine, a drug used to treat human African trypanosomiasis (HAT) (19). Moreover, the importance of amino acid transporters in T. brucei has been demonstrated by RNAi-mediated knock-down of arginine and lysine transporters TbAAT5-3 and TbAAT16-1 from the AAAP family which resulted in growth arrest in bloodstream forms (20). In Leishmania donovani , the transporter LdAAP24 mediates proline and alanine uptake and regulates the response to osmotic stress and amino acid homeostasis (21).…”
Section: Introductionmentioning
confidence: 99%